Law Enforcement of Narcotics Abuse: Case Study of Investigation Process in Narcotics Criminal Acts in The Kolaka District National Narcotics Agency - Basrawi, Basrawi; Sukri, Sukri; Eka Mayasari, Riezka (Journal of Progressive Law and Legal Studies, 2023)
Narcotics abuse recently has always increased, not only among adults but also among adolescents and children. The cause of this abuse consists of two factors, namely factor internal and external. Therefore, cases of drug abuse are increasing every year. This study was conducted with the aim to find out the form of law enforcement against narcotics abusers in the process of investigating narcotics crimes. The research method used in this study was normative juridical approach which is supported by empirical juridical by detailing the description and collecting primary data through interviews. The results of this study show that there are two forms of law enforcement against narcotics abusers, namely repressive law enforcement and rehabilitative law enforcement as regulated in Law Number 35 of 2009 concerning narcotics. Based on the interviews conducted, it is known that there are several obstacles in law enforcement on narcotics cases at the Kolaka National Narcotics Agency, namely the lack of personnel, the unresponsive community in providing information to investigators as the key to successful law enforcement and decreasing of operational costs in supporting facilities and infrastructure